Organ weights and ratios for postmortem identification of fetal growth restriction: utility and confounding factors. (25th October 2016) - Man, J.; Hutchinson, J. C.; Ashworth, M.; Jeffrey, I.; Heazell, A. E.; Sebire, N. J.
ABSTRACT: Objectives: The postmortem fetal brain:liver weight ratio is commonly used as a marker of nutrition for diagnosis of fetal growth restriction (FGR). However, there are limited data regarding the effects of intrauterine retention, fetal maceration and postmortem interval on organ weights and their ratios at autopsy. Our aims were to examine the relationships between gestational‐age‐adjusted and sex‐adjusted fetal organ weights at autopsy, cause of intrauterine death and effects of intrauterine retention, and to determine whether the brain:liver weight ratio is a reliable marker of FGR in intrauterine death. Methods: As part of a larger study examining autopsy findings in intrauterine death, data from two specialist centers in London were collated in a specially designed database. Autopsy and clinical information for > 1000 intrauterine deaths between 2005 and 2013 were extracted. Adjusted (delta) organ weights were calculated by plotting against gestational age female and male brain, liver, thymus, heart, combined kidney, combined lung, spleen and combined adrenal gland weights. Polynomial regression was used to determine best fit and to calculate expected (50 th centile) organ weights and deviations from expected. We compared adjusted organ weights and body:organ weight ratios in fetuses which were small‐for‐gestational age (SGA) at autopsy (birth weight < 10 th centile for normal live births) vs those in fetuses which were not, and in macerated vs non‐macerated fetuses. Results: The majority of fetal organs (brain, liver, heart, thymus, lungs, kidneys and thyroid) in SGA fetuses were significantly lighter than those in non‐SGA fetuses. Body:organ weight ratios for thymus, liver and spleen were significantly greater in SGA fetuses, indicating these organs to be disproportionately small. The majority of organs were significantly lighter in macerated compared with non‐macerated fetuses and body:organ weight ratios for most organs (liver, thymus, lung, pancreas, adrenal gland, kidney, heart) were significantly greater in macerated compared with non‐macerated fetuses. When SGA cases with demonstrable placental histological abnormalities were compared with other SGA cases, there was a significant difference in the brain:liver weight ratio (median, 6 vs 3.5). Conclusion: Changes after intrauterine death lead to loss of fetal weight, with preferential weight loss of visceral organs such as the liver. Maceration therefore affects the brain:liver weight ratio and adjustment should be made for such changes during interpretation of ratios. Fetal organ weights may be affected significantly by mechanism of death and postmortem changes. The fetal brain:liver weight ratio may provide useful information regarding intrauterine growth status at time of death, provided that adjustment is made for effects of intrauterine retention and that appropriate cut‐off values are used. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from theabstract to view the translations. This article has been selected for Journal Club. Clickhere to view slides and discussion points.